The American Psychological Association: A Historical Perspective. 1992
DOI: 10.1037/10111-012
|View full text |Cite
|
Sign up to set email alerts
|

The APA knowledge dissemination program: An overview of 100 years.

Abstract: Scientific and professional societies have existed historically to define a field and facilitate communication within it. Two major information dissemination channels have been the hallmark of these activities by societies: annual conventions and publications. The publications developed and disseminated through such societies may be pamphlets intended for useThe author gratefully acknowledges the assistance of many APA staff in the preparation of this chapter. Elizabeth Bulatao of the Office of Communications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
7

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 35 publications
3
136
0
7
Order By: Relevance
“…Data also suggest that the average size of (i.e., the number of citations within) each in-groups citation had expanded over time. The timing of this increased volume of citations corresponded to the wider availability of PsycLIT and PsycINFO on CD-ROMs in the mid-1980s (VandenBos, 1992) and the subsequent expansion of the databases to the historical literature back to 1887.…”
Section: Resultsmentioning
confidence: 99%
“…Data also suggest that the average size of (i.e., the number of citations within) each in-groups citation had expanded over time. The timing of this increased volume of citations corresponded to the wider availability of PsycLIT and PsycINFO on CD-ROMs in the mid-1980s (VandenBos, 1992) and the subsequent expansion of the databases to the historical literature back to 1887.…”
Section: Resultsmentioning
confidence: 99%
“…Trauma is an event in which a person witnesses or experiences a threat to his or her own life or physical safety or that of others and experiences fear, terror, or helplessness (VandenBos, 2007). Sixty to ninety percent of the general population has experienced traumatic events (Breslau, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The title "Publication Manual" was first used in 1952, and new revisions followed in 1957, 1967, 1974, and 1983. By 1990, annual sales exceeded 200,000 copies (VandenBos, 1992). The 1994 revision is 368 pages.…”
Section: Apa Style and Paradigmatic Thinkingmentioning
confidence: 99%
“…It has evolved along with psychology. VandenBos (1992) reported that the APA began its journals program in 1923. By 1929, an APA committee printed a seven-page writer's guide in the Psychological Bulletin.…”
Section: Apa Style and Paradigmatic Thinkingmentioning
confidence: 99%
See 1 more Smart Citation